A Comparative Study and Assessment of Burn Wound Sepsis Using Surface Swab, Fine Needle Aspiration and Wound Biopsy Cultures - Dhanraj, Prema; Korula, Philip; Lalitha, M K; Stanley, Sulochana (Indian Journal of Plastic Surgery, 1994)
The purpose of this study was to evaluate a simple standardized fine needle aspiration method for bacteriologic assessment of burn wound and to determine whether this method is as reliable and useful as the classic invasive biopsy culture method1. Considering the high correlation with the organism in all three methods, viz. swab, aspiration and wound biopsy culture techniques, we feel fine needle aspiration culture has a place in bacteriological assessment of burn wound as it is simple, easy and less painful compared to the more conventional wound biopsy culture technique.